Penerapan Modul dan Pembelajaran Adaptif dalam Kurikulum Merdeka : Tantangan dan Solusi - Nazwa Dewi Tianda; Delfi Wulandari; Lidwina Roulina Turnip (Lembaga Pengembangan Kinerja Dosen, 2025)
The Independent Curriculum provides thinking in learning, allowing teachers to adjust the material to the needs of students. However, challenges such as limited resources, teacher readiness, and variations in student learning styles are still challenges in its implementation (Kemendikbud, 2022). This study aims to examine the implementation of adaptive learning modules as a solution to improve learning effectiveness. Adaptive modules that integrate technology and personalization of teaching materials are expected to improve students' understanding in a way that is more appropriate to their individual needs (Mayer, 2009). The approach used in this study includes literature studies and field observations, which show that adaptive modules can significantly improve student learning outcomes. However, the implementation of this adaptive learning module still requires support in the form of adequate teacher training and supporting technological infrastructure so that learning can run effectively and efficiently (Batubara, 2019). This study provides recommendations to strengthen teacher readiness and provide the resources needed in the implementation of adaptive modules.